Poezja i antypoezja. Komentarze do Psalmu 120 a strategia przekładu - Jerzy Brzozowski (Ksiegarnia Akademicka Publishing, 2019)
Poetry and Anti-Poetry: A Commentary to Psalm 120 and Translation Strategy The main purpose of this paper dedicated to those Polish Bible scholars who seem to ignore new achievements of the theory of translation is to show that a conscious definition of the translation strategy (most notably, its scopos and its projected reader) is a capital issue in the Bible translation studies. The author aims to convince persons who may not be devoted admirers of poetry – a frequent case among Bible scholars – that poetry should not anymore be considered merely a “beautiful form” supplementing the omnipotent sense anymore. In his analysis of the first and successive editions of the Millenium Bible the author criticizes the commentaries to the Psalms which he calls “antipoetic” and therefore dissonant with the translated texts.